Music and Women's Fight Against Gender Injustice in Voice of Baceprot’s 'PMS' Lyrics - Rakhmat Agung Pramadani; Arizal Mutahir; Wiman Rizkidarajat (Al Huwiyah: Journal of Woman and Children Studies, 2025)
Music, as a form of literature, can serve as a medium for critiquing social phenomena, including gender inequality. The gender inequality experienced by women is extremely detrimental and has a negative impact on them. Voice of Baceprot, a hijab-wearing female metal band from Garut, West Java, is one of the musicians who use their song lyrics to deconstruct the phenomenon of gender inequality. The purpose of this study is to identify the meaning and message contained in the lyrics of the song “PMS” by Voice of Baceprot in the context of women's struggle against gender inequality. The method of this study is descriptive qualitative, using Sara Mills' critical discourse analysis approach. The research data consists of the lyrics contained in the song PMS by Voice of Baceprot. Data collection techniques were carried out by repeatedly listening to the song and noting down the lyrics. The collected data was then analyzed using Sara Mills' Critical Discourse Analysis theory. The results of the study show that the lyrics contained in this song express women's rejection and resistance as subjects against patriarchal society as objects. Readers or listeners are positioned by the author through the lyrics as being in two positions: either as those who fight for women's freedom or as those who perpetuate injustice against women. Keywords: Woman, Oppresion, Voice of Baceprot.